Communicating livestock disease risks in Ngamiland: the case of contagious bovine pleuropneumonia. Issue 2 (4th May 2019) - Thakadu, Olekae Tsompi; Reetsang, Naledi Pearl
ABSTRACT: Livestock contributes to the socio-economic livelihoods of many communities around the world and national economies. Contagious bovine pleuropneumonia (CBPP) is a global phenomenon that affects human livelihoods; it has been an issue of concern for its tendency to recur in places where it was previously eradicated. This study aims at exploring the effectiveness of communication interventions towards mitigation livestock disease risks in Ngamiland district, using the 1995 CBPP disease outbreak as a case. The study, guided by the Relational Theory of Risk, used a sample of 93 respondents whose cattle were slaughtered in 1996. Results point to multiple factors which may have promoted lack of adoption and compliance by the community after being informed about CBPP recurrence in 1995. These include; time factor it took after the previous outbreak (56 years), myths, believes, perceptions towards CBPP outbreak in the district by different ethnic groups and conflicting information disseminated by other stakeholder sources. Findings also reveal high perceptions of CBPP risks, with respondents demonstrating a good knowledge of the livestock diseases. The study found that a multi-mix approach to communication was used in risk communication. The study recommends participatory epidemiology and communication approaches that may facilitate improved risk management and communication.